Simulation Research on Static and Dynamic Behavior of M-STATCOM - Rizwan Jafri; Zha Xiaoming; S Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper, a novel static synchronous compensator/condensor based on the state-of-the-art modular multilevel converter called M-STATCOM is introduced. In order to support bus bar voltage, maintain the stability of DC-link capacitor voltage, obtain harmonics free output voltage and compensate reactive power under unbalanced operation, a novel direct current control (DCC) technique is proposed. For high accuracy and good control system response purpose Level-shift sine pulse width modulation (LS-PWM) technique is selected as the modulation strategy. The M-STATCOM is simulated in PSCAD/EMTDC environment and its static and dynamic responses are discussed. The effectiveness and feasibility of the proposed modulation and control strategy is validated by the simulation results.